Design and synthesis of 3-arylbenzopyran based non-steroidal vitamin-D3 mimics as osteogenic agents12. Issue 12 (17th October 2016) - Ahmad, Mohd. Imran; Raghuvanshi, Dushyant Singh; Singh, Sarita; John, Aijaz A.; Prakash, Ravi; Nainawat, Kripa Shankar; Singh, Divya; Tripathi, Shubhandra; Sharma, Ashok; Gupta, Atul
Abstract : 27b enhanced osteoblast differentiation at 1 pM in mouse calvarial osteoblast cells without inherent toxicity. Abstract : 3-Arylbenzopyran based non-steroidal osteogenic agents have been explored as structural templates of estrogen and vitamin-D3 . The target molecules18a–c, 19a–c, 26a–c, 27a–c and intermediates17a–c and25a–c were studied for their osteogenic activity in an osteoblast differentiation assay in vitro using mouse calvarial osteoblast cells. Compounds25c, 26b, 27b and27c effectively increased ALP activity at 1 pM concentration compared to the untreated cells. The active compounds were devoid of inherent toxicity at 1 pM concentration in osteoblast cells. The most active compound, 27b, was studied for mineralization of osteoblast cells and expression of marker genes, viz. BMP-2, RUNX-2 & Osx, involved in osteogenesis. Molecular docking analysis performed for27b showed its possible interactions with estrogen receptor-α and -β (ER-α and ER-β) as well as the vitamin-D receptor (VDR).